The effectiveness of integrating artificial intelligence in virtual laboratories on achievement and attitudes Physics students at Al-Zawiya University and the challenges of its application (Al-Farooq Journal of Sciences, 2026)
Used in this research Virtual laboratories integrated with artificial intelligenceTo determine their impact on the academic achievement of physics students at Al-Zawiya Universityand recognitionOn their trends towards integrating artificial intelligenceIn virtual laboratories  and the challenges they faceand an attempt to present a number of Recommendations and suggestions for overcoming them.The results have proven the effectiveness of integrating artificial intelligence.In virtual laboratoriesIn improving the academic level and the superiority of students in their results compared to students who were taught using the traditional method.,andShowedThe research results show that students have positive attitudes towards integrating artificial intelligence.In virtual laboratoriesThe students' positive attitudes were high, with a mean score of (4.32) and a percentage of (86.46%), and showedThe results also showed that the challenges they faced had an arithmetic mean of (2.54) and a percentage of (50.8%).  This is a positive sign that proves that these obstacles were not a fundamental impediment to students' use and interaction with the smart laboratory experiment and their strong desire to use it in teaching physics.
Keywords: Artificial intelligence, virtual laboratories, achievement, trends, physics